Pemetaan Persepsi Konsumen untuk Meningkatkan Daya Saing Produk: Studi Kasus T-shirt Libre Everyday - Lastanila, Selly; Rohayati, Yati; Sagita, Boby Hera (Ekonomis: Journal of Economics and Business, 2024)
In competing, it is important to understand consumer perceptions of products. Even though consumers are satisfied with the company's brand image, the company can still lose its customers. Companies need to identify consumer characteristics in their marketing strategy, because this can help formulate the right position for the product. Understanding the concept of product or brand positioning is very important to maintain the company's continuity in competition. This research aims to determine product positioning based on consumer perceptions of product attributes. Consumer perception mapping was carried out on the Libre Everyday t-shirt product using a purposive sampling method involving 70 respondents who had been t-shirt users for more than two years and were familiar with at least three specified t-shirt brands. The data obtained was processed using IBM SPSS 23 software to produce perceptual mapping. The calculation results show that this perception map model is feasible and acceptable, as proven by the goodness of fit test with an R-square value of 0.15312 and a stress value of 0.97814. This perception map depicts brand positioning, product attributes, and closest competitors. To increase product competitiveness, it is necessary to improve product positioning by utilizing superior product attributes, improving marketing communications, and adding marketing channels.